Enemy [videorecording (DVD)] - Gyllenhaal, Jake, 1980-; Laurent, Mélanie, 1983-; Gadon, Sarah, 1987-; Rossellini, Isabella; Gullón, Javier; Saramago, José (2014)
Adam Bell, a glum, disheveled history professor who seems disinterested even in his beautiful girlfriend Mary. Watching a movie on the recommendation of a colleague, Adam spots his double; a bit-part actor named Anthony St. Clair, and decides to track him down. The identical men meet and their lives become bizarrely and irrevocably intertwined.